Representasi Makna Konten Komunitas Keagamaan di Instagram Majelis Satu Rasa (Studi Semiotika Roland Barthes pada Instagram Majelis Satu Rasa) - Fauzan Ghilar Ibrahim; Dina Alamianti; Imam Jahrudin Priyanto (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the representation of the religious community Majelis Satu Rasa as portrayed through photo and video content on its Instagram account. The research is motivated by the growing use of social media, particularly Instagram, not only as a means of personal communication but also as a medium of da'wah utilized by religious communities to construct identity and image in the digital sphere. A descriptive qualitative method combined with Roland Barthes' semiotic approach was employed to examine the denotative, connotative, and mythical meanings embedded in six selected photo and video contents. Data were collected through observation of Instagram posts, interviews with the account administrator and congregation members, and visual documentation, with validity established through source, technique, and time triangulation. The findings show that at the denotative level, the published content portrays religious study activities, congregational togetherness, social action, and reflections on daily life presented through engaging visuals. At the connotative level, the content represents religiosity, social concern, self-reflection, optimism, and solidarity. At the mythical level, the content constructs the understanding that religion is a guide that brings inner peace, that repentance is a path toward self-improvement, and that caring for others is part of Islamic teaching. These findings indicate that Majelis Satu Rasa successfully represents itself as a religious, humanistic, modern community close to younger audiences, while confirming Instagram's role as a space of representation that constructs meaning, identity, and image for religious communities in the digital era.